KEHIDUPAN GURU DAN MURID DENGAN BEBERAPA ASPEK DAN KARAKTERISTIKNYA PADA PERIODE KLASIK (571-750 M) - M. Agus Kurniawan (Jurnal Ilmiah AZZIQRI: Kajian Keislaman dan Kependidikan, 2021)
At the time of Caliph Abu Bakr As-Siddiq basically not much different with future educational Prophet. However, since the Caliph Umar bin Khattab more education increases, the teachers have been appointed and in salaries to teach in areas newly conquered. At the time of Uthman education handed over to the people and companions (to lift the teacher) and then spread to teach every aspect of the area. While at the time of Caliph Ali bin Abi Talib, the education received less attention due to polical conflicts that always happens. The Umayyad Dynasty (661-758 AD). The pattern of education during the Umayyad Dynasty seems to be different from the pattern of education during the time of the Prophet Muhammad and KhulafaurRashidin, because during this period various advances have been made, including in the economic field. Some of the teachers' life conditions at that time began to get attention, because among the authorities (government) paid or paid teachers to teach their sons, there was even a place to live in the palace. But for teachers who teach students with weak economic backgrounds, whose places are in the mosque grounds, they are not as big-paying as teachers who teach children of rulers in the palace, but only get appreciation from the community. The pattern of education at that time was still the Kuttab system centered on mosques, palaces, and teachers' homes. On the other hand, Islamic civilization, especially Arabic, has been able to go international as the official language of the country, especially on the continents of Europe, Africa, and Asia.